Revisiting students’ foreign language learning demotivation: From concepts to themes - Gao, Lixiang; Liu, Honggang (Frontiers in Psychology, 2022)
Revisiting Students' Foreign Language Learning Demotivation is a common psychological phenomenon in foreign language learning. Having a good understanding of learners’ foreign language learning demotivation is conducive to enriching the fruits of psychological research on foreign language learning theoretically and practically by exploring effective ways to improve learners’ foreign language learning motivation. Therefore, this study entails an analysis of the selected literature from 2001 to 2021 to interpret the concept of foreign language learning demotivation, illustrate the research topics from the classification of demotivators and their relationships with other psychological factors, and fully describe the research methods and participants. Future research should expand theoretical perspectives, include more participants of different grades, and adopt multiple research methods.